Genome Wide Prediction, Mapping and Development of Genomic Resources of Mastitis Associated Genes in Water Buffalo - Jaiswal, Sarika; Jagannadham, Jaisri; Kumari, Juli; Iquebal, Mir Asif; Gurjar, Anoop Kishor Singh; Nayan, Varij; Angadi, Ulavappa B.; Kumar, Sunil; Kumar, Rakesh; Datta, Tirtha Kumar; Rai, Anil; Kumar, Dinesh (Frontiers in Veterinary Science, 2021)
Water buffalo (Bubalus bubalis), is a very important animal resource which contributes milk, meat, leather, dairy products and power for ploughing and transport. However mastitis, a bacterial disease affecting milk production and reproduction efficiency, is most prevalent in populations having intensive selection for higher milk yield, especially where inbreeding level is also high. Climate change and poor hygiene management practices further implicate the issue. The management of this disease has major challenges, like antibiotic resistance, maximum residue level, horizontal gene transfer and limited success in resistance breeding. Bovine mastitis genome wide association studies have limited success due to breed differences, sample sizes and minor allele frequency, lowering the power to detect disease associated with SNPs. In this work, we focused on the application of targeted gene panels (TGPs) in screening for candidate gene association analysis, and how this approach overcomes the limitation of genome wide association studies. This work will facilitate the targeted sequencing of buffalo genomic regions with high depth coverage required to mine extremely rare variants potentially associated with buffalo mastitis. Though, whole genome assembly of water buffalo is available but neither mastitis genes are predicted nor TGP in the form of web-genomic resource is available required for future variant mining and association studies. Out of 129 mastitis associated genes of cattle, 101 were completely mapped on buffalo genome to make TGP. It further helped in identifying rare variants in water buffalo. Eighty-five genes were validated in buffalo gene expression atlas having RNA-Seq data of 50 tissues. Functions of 97 genes were predicted revealing 225 pathways. The mastitis proteins were used for protein-protein interaction network analysis to obtain additional cross-talking proteins. A total of 1306 SNPs and 152 indels were identified from 101 genes. Water Buffalo-MSTdb was developed with 3-tier architecture to retrieve mastitis associated genes having genomic coordinates with chromosomal details for TGP sequencing for mining of minor alleles for further association studies. Lastly, a web-genomic resource is made available to mine variants of targeted gene panels in buffalo for mastitis resistance breeding in endeavor to ensure improved productivity and reproductive efficiency of water buffalo.